Adults with adverse childhood experiences report greater coronavirus anxiety - Vrinda Kalia; Katherine Knauft (PLoS ONE, 2025)
Background Adults with early life adversity exhibit heightened response to threat signals in the environment, which makes them vulnerable to developing stress-related mental health problems, including anxiety disorders. Yet, the impact of the COVID-19 pandemic on adults who have experienced early life adversity is understudied. Recently, researchers have characterized dysfunctional cognitions about the pandemic, which are associated with negative mental health outcomes, as coronavirus anxiety. We conducted a study to examine the relation between exposure to early life adversity, perceived threat from COVID-19, and coronavirus anxiety. Methods Adults (N = 975; 18–78 years of age; 585 = Women) living in the United States were recruited online in October 2020. Two forms of early life adversity, maltreatment and household dysfunction, were assessed using the Adverse Childhood Experiences scale. Participants’ state anxiety was measured using the State-Trait Anxiety Inventory, and coronavirus anxiety was measured via the Coronavirus Anxiety Scale. Three items were used to measure perceived threat from COVID-19. Additionally, as reduced flexibility is implicated in the development and maintenance of anxiety disorders, participants’ cognitive flexibility was assessed using the Cognitive Flexibility Inventory. Results The data were analyzed using parallel mediation regression analyses. Exposure to early life adversity, in the form of maltreatment and household dysfunction, were the key predictor variables. Coronavirus anxiety and state anxiety were the outcome variables. Perceived threat from COVID-19 and cognitive flexibility were added as parallel mediators into all the regression models. The regression analyses revealed that both perceived threat from COVID-19 and cognitive flexibility mediated the relation between early life adversity and anxiety. The data demonstrate that exposure to early life adversity, in the form of maltreatment or household dysfunction, was associated with higher levels of perceived threat from COVID-19, which, in turn, predicted increased coronavirus anxiety and state anxiety. In contrast, appraisal of everyday challenges as controllable, one of the two types of cognitive flexibility assessed, predicted lower levels of coronavirus anxiety and state anxiety. However, exposure to maltreatment and household dysfunction was associated with reduced cognitive flexibility. Conclusion This study replicates and extends prior research showing that adults with early life adversity experienced increased anxiety during the pandemic. The findings bolster existing theories that highlight the importance of threat appraisal as a mechanism for the development of anxiety disorders in this population. Additionally, this report adds to the limited body of work on the impact of COVID-19 in adults who have experienced early life adversity.